Widespread occurrence of populations of the unique autotrophic ciliate Mesodinium rubrum (Ciliophora: Haptorida) in brackish and saline lakes of the Vestfold Hills (Eastern Antarctica) - Perriss, SJ; Laybourn-Parry, J; Marchant, HJ (1997)
No description available